Pengembangan Media Pembelajaran Explosion Box pada Tema Menuju Masyarakat Sejahtera Kelas VI SD - Tarigan, Fima Ega Dita Br; Yarshal, Dinda (Indonesian Research Journal on Education, 2023)
The background of this research is that there are still several obstacles, such as, the learning process carried out by educators when viewed in terms of the media is still less varied, at the time of learning the teacher only explains and students only listen to explanations from the teacher, so that students' thinking skills in the learning process in class VI have not As a result, students' thinking skills are still lacking. With the Explosion Box, students are more interested and motivated in teaching and learning activities. The research conducted by the author, namely Research Hand Development (R&D) research which was carried out in several stages, namely (1) Analysis (Analysis) The analysis phase carried out includedthree things, namely needs analysis, curriculum analysis, and character analysis of students (2) Design (Design) References in the preparation of making picture story book media are product specifications that have been made, (3) Development (Development). At this stage the development of the media will be tested for validity by media experts, material experts and teachers. Based on the results of the validationof the teacher's response which is divided into 4 aspects, the overall assessment of the teacher's response to the media obtained a percentage of 95%. The results of the media expert's validation are divided into 5 aspects, the overall assessment of the media expert's review gets a percentage of 82%. And the results of material expert validation which are divided into 5 aspects, the overall assessment of the media expert's review gets a percentage of 92%. The overall percentage of learning experts is quite feasible, while media experts and material experts are eligible to be used as media in the learning activities of sixthgrade elementary school students with the theme towards a prosperous society.